2016
DOI: 10.1002/bem.21994
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐sowing static magnetic field treatment for improving water and radiation use efficiency in chickpea (Cicer arietinum L.) under soil moisture stress

Abstract: Soil moisture stress during pod filling is a major constraint in production of chickpea (Cicer arietinum L.), a fundamentally dry land crop. We investigated effect of pre-sowing seed priming with static magnetic field (SMF) on alleviation of stress through improvement in radiation and water use efficiencies. Experiments were conducted under greenhouse and open field conditions with desi and kabuli genotypes. Seeds exposed to SMF (strength: 100 mT, exposure: 1 h) led to increase in root volume and surface area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Similar findings were also reported by Selim and El-Nady [ 6 ] in tomato under magnetic treatment in response to drought stress. Nilimesh et al [ 57 ] documented that presowing magnetic field treatment increases carotenoid content in chickpea under soil moisture stress. Furthermore it is important to note that North Root treatment tend to have maximum chlorophyll contents as compared to other magnetism treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also reported by Selim and El-Nady [ 6 ] in tomato under magnetic treatment in response to drought stress. Nilimesh et al [ 57 ] documented that presowing magnetic field treatment increases carotenoid content in chickpea under soil moisture stress. Furthermore it is important to note that North Root treatment tend to have maximum chlorophyll contents as compared to other magnetism treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic treatment as a noninvasive technique with high efficiency and low cost has been used in agriculture for many years (Mridha et al 2016;Xie et al 2009) to promote the soil microenvironment and improve plant growth. Previous studies have indicated that magnetic treatment induced some changes in the water (Chibowski and Szczé 2018), such as breaking hydrogen bonds, increasing viscosity, enhancing nutrient solubility, and decreasing the contact angle (Maheshwari and Grewal 2009;Evelyn et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Seed priming is a technique to stimulate seed metabolic processes during germination and improve their performance under diverse environmental conditions [ 7 , 8 ]. Magnetopriming is a non-invasive dry seed priming treatment that has been widely used to enhance seedling vigor and plant growth under various environmental cues [ 9 , 10 , 11 , 12 , 13 ]. It can improve seedling growth under various abiotic stresses (drought, salt, heavy metal toxicity and UV-B stress) via increased metabolic processes like α-amylase, protease, nitrate reductase and nitric oxide synthase-like activities during germination [ 9 , 12 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%